2020
DOI: 10.1016/j.heliyon.2020.e03946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with malaria in children under five years of age in Malawi, using malaria indicator survey data

Abstract: Background: Malaria remains a public health problem in developing countries and Malawi is no different. Although there has been an improvement in reducing malaria in Malawi, it remains a problem, especially in children less than five years old. The primary objective of the study was to assess whether socio-economic, geographic and demographic factors are associated with malaria, using the generalized additive mixed model (GAMM). Data and methodology: The study used a 2017 dataset from the Malawi Malaria Indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 38 publications
10
34
1
Order By: Relevance
“…Based on the VIF test, we found that the nonlinear feature is more significant about the association with meteorological factors and COVID-19 cases. GAMM is used to explore the nonlinear relationship between weather factors and health conditions [21,22]. Since temperature may last for several days and the incubation period of COVID-19 varies from 1 to 14 days, we used GAMM to test the moving average hysteresis effect of temperature differences (lag0-4).…”
Section: Generalized Additive Mixed Model (Gamm)mentioning
confidence: 99%
“…Based on the VIF test, we found that the nonlinear feature is more significant about the association with meteorological factors and COVID-19 cases. GAMM is used to explore the nonlinear relationship between weather factors and health conditions [21,22]. Since temperature may last for several days and the incubation period of COVID-19 varies from 1 to 14 days, we used GAMM to test the moving average hysteresis effect of temperature differences (lag0-4).…”
Section: Generalized Additive Mixed Model (Gamm)mentioning
confidence: 99%
“…Only children aged 0-59 months from the mothers who stayed in or visited the household the night before the 2014 survey were included. The present study used the children's file record and a total weighted number of 3112 children were drawn as a sample size to demonstrate a national-level representation (MOHSW and ICF, 2016;Gaston and Ramroop, 2020). The weighted samples were used to achieve the standard that is descriptive of the nation and accounts for the complex sample design from the data.…”
Section: Data Source and Sampling Techniquesmentioning
confidence: 99%
“…The population in each region did have not the same weight and the individuals surveyed in each region should contribute equivalently to the size of the total number in each region. To overcome this problem of unweighted, the present study used a weighted sample size (MOHSW and ICF, 2016;Gaston and Ramroop, 2020).…”
Section: Data Source and Sampling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria remains one of the most significant causes of morbidity and mortality in resource poor countries especially in sub-Sahara African children under the age of five years and pregnant women (1,2). According to WHO malaria report in 2015, malaria was prevalent in more than 90 countries of the tropical and semitropical world (Africa, Amazon, central and southern America; central, south and south east Asia; Pacific) that are home to more than half of the world's people and it is still a persistent problem in most of these areas (3).…”
Section: Introductionmentioning
confidence: 99%